Design and performance of GaSb-based quantum cascade detectors - Giparakis Miriam; Windischhofer Andreas; Isceri Stefania; Schrenk Werner; Schwarz Benedikt; Strasser Gottfried; Andrews Aaron Maxwell (Nanophotonics, 2024)
InAs/AlSb quantum cascade detectors (QCDs) grown strain-balanced on GaSb substrates are presented. This material system offers intrinsic performance-improving properties, like a low effective electron mass of the well material of 0.026 m 0, enhancing the optical transition strength, and a high conduction band offset of 2.28 eV, reducing the noise and allowing for high optical transition energies. InAs and AlSb strain balance each other on GaSb with an InAs:AlSb ratio of 0.96:1. To regain the freedom of a lattice-matched material system regarding the optimization of a QCD design, submonolayer InSb layers are introduced. With strain engineering, four different active regions between 3.65 and 5.5 µm were designed with InAs:AlSb thickness ratios of up to 2.8:1, and subsequently grown and characterized. This includes an optimized QCD design at 4.3 µm, with a room-temperature peak responsivity of 26.12 mA/W and a detectivity of 1.41 × 108 Jones. Additionally, all QCD designs exhibit higher-energy interband signals in the mid- to near-infrared, stemming from the InAs/AlSb type-II alignment and the narrow InAs band gap.